Globalizacijske zahteve v liturgičnih obredih - Fabijan, Silvester (Bogoslovni vestnik, 2003)
The globalization dimension of the liturgical ritual is multi-layered. On the one hand, there can be seen the spiritual-liturgical demands of globalization, which are already indicated in the texts of the New Testament, especially in the demand to worship "in spirit in truth" and in the essence itself of liturgical spirituality, which is peculiar to the Church and is the "source and peak" of all Christian life. On the other hand, the unification and thereby the globalization dimension of the ritual was also influenced by external factors, thus by the newly established patriarchal centres, by the demands of the popes and the emperors for unification, which was reflected in the romanization of the rites and in the introduction of the official liturgical (Latin) language, and by the mendicant orders with their uniform liturgy that they spread because they were not bound to a certain place. The peak of globalization demands are certainly the post-Tridentine liturgical books and the establishing of a uniform central liturgical authority i.e. the Sacred Congregation of Rites that has been directing and controlling the liturgical life of the Church. Though the demands of the Synod of Pistoia and of the liturgical movement, expecially the demand to introduce national languages into the liturgy, are deglobalization demands and also the liturgical renewal of the Second Vatican Council is antiglobalizational in certain segments, we have to be aware that every renewal also globalizes in its own way when it influence the manner of celebrating the liturgy.
Keywords: globalizacija; globalization; liturgična duhovnost; liturgična obrednost; liturgični jezik; liturgika; romanizacija bogoslužja